Experimental Study on the Effect of Aggregate Content on the Compressive Strength of Fly Ash-based Geopolymer Concrete - Z, Yosafat; Herwani, Herwani; Faisal, Faisal (Fakultas Teknik Universitas Tanjungpura, 2025)
The production process of Portland cement causes air pollution by releasing carbon dioxide into the air, contributing to the greenhouse effect. In an effort to reduce cement usage, researchers are seeking more environmentally friendly materials, such as fly ash a byproduct of coal combustion as an alternative to cement. In this study, fly ash is used to replace cement in geopolymer concrete. The method used in this research is the experimental method, involving the creation of test specimens to examine physical and mechanical properties, including material analysis, specimen preparation, curing, compressive strength testing, split tensile strength, and modulus of elasticity. The study results show that the average bulk density ranges from 2,206.949 kg/m ³ to 2,313.052 kg/m ³, the average compressive strength ranges from 8.913 MPa to 15.915 MPa, the average split tensile strength ranges from 0.943 MPa to 1.368 MPa, and the average modulus of elasticity ranges from 2,186.062 MPa to 3,644.775 MPa. The best variation was found in geopolymer concrete with 60% fine aggregate content, achieving an average compressive strength of 15.915 MPa at 28 days. The study concludes that fly ash has strong potential to replace cement as the main component in concrete.